The mediating effect of enterprise risk management practices on organizational attributes and organizational performance / Azreen Roslan - Roslan, Azreen (2016)
Risk is inherent in all organizations, but if inefficiently managed will affect the confidence and expectations of the stakeholders. The development of an enterprise risk management (ERM) program enables organizations to manage corporate risks in a holistic manner as opposed to the silo-based perspective in traditional risk management frameworks. ERM is a best practice technique to evaluate and manage risks in an integrated manner to cater to the new economic reality. Further, ERM is a management tool to assist top management to make informed decisions. Past studies have established positive effects of ERM practices, as organizations are better prepared to manage their feasible threats in a holistic and integrated manner. In fact, there are general consensuses of researchers that organizations practicing ERM are found to perform better due to the fact that such organizations are able to ensure that the total risks facing their organization are well managed. More specifically, their current, future and emerging risks are identified and controlled to allow the organization to achieve their strategic objectives. For this to happen, top management support is crucial to drive ERM and ensure better organizational performance. However, evidence pertaining to this is still scarce. As such, this research aims to provide a better understanding of the influence of organizational attributes on the extent of ERM practices towards organizational performance. A research model is developed to examine and evaluate the attributes of ERM practices and its influence on organizational performance. In addition, two underpinning theories namely Agency theory and Contingency theory are used to justify these relationships. The existing empirical evidence with regard to the risk management activities of nonfinancial organizations were collected, in order to gain insight into the extent of ERM practices. A questionnaire survey technique is employed to collect data from the public listed of non financial companies. 102 useable responses were received and further analyzed using the appropriate statistical procedures. The research model was then tested using the partial least squares (PLS) technique. Smart PLS 2.0M3 was used to validate the research model and test the proposed research hypotheses. The empirical results of this research lead to several significant findings. This study confirms that ERM practices positively influences organizational performance. Under the construct of organizational attributes, organizational structure and role clarity are found to have significant positive relationship with the extent of ERM practices. However, the result does not support hypothesized relationships between board composition (board independence and role separation) and the extent ERM practices. In addition, findings showed that the extent of ERM practices mediates the relationship between organizational structure and role clarity with organizational performance. However, the findings showed that the extent of ERM practices does not mediate the relationship between board composition and organizational performance. Theoretically, this study provides further insights on the attributes and outcomes of the extent of ERM practices within Malaysia public listed of non financial companies' context. Methodological and managerial implications were discussed and several possible avenues for future research were identified and proposed. In short, the findings of this study shed new light to the existing ERM literature and provide better assurance to the industry practitioners on the significance of ERM practices in the organization.